Actividad antiviral in vitro de extractos de Hura crepitans y Codiaeum variegatum en la replicación de herpes virus bovino tipo-1 y virus de estomatitis vesicular (2007)
ABSTRACT: Leaves from Hura crepitans and Codiaeum variegatum plants were collected in Medellín, Colombia to determine its cytotoxic [CA] and antiviral activity [AVA]. Four extracts were prepared using hexane, ethyl acetate, methanol and water; the antiviral activity was tested against Vesicular Stomatitis Virus (VSV), serotypes Indiana and New Jersey and Bovine Herpes Virus (type 1 Bogotá strain). The preliminary biological activity of each of the eight extracts was determined on BHK-21 cell monolayers using 96 well-plates. Then, promissory extracts were further tested using the MTT [3-(4,5-dimethylthiazol–2-yl)-2,5-diphenyltetrazolium bromide] assay to determine the cytotoxic concentration 50 (CC50), the inhibitory concentration 50 (IC50 ), and the selectivity index (SI). None of the evaluated plants exhibited AVA against VSV, whereas the extracts in hexane, ethyl acetate and methanol from Hura crepitans protected cell monolayer from infection against BHV-Bogotá with IC50 of 17.41, 7.87 and 2.75 g/ml respectively. The best IS was hexane of H. crepitans (SI > 17.4). These results suggest that this extract contains antiviral compounds. This research is pioneer demonstrating AVA against BHV-1B in extracts from plants of the Euphorbiaceae family.